Serum Testosterone Level in Female Patients with Adult Acne and Its Correlation with Acne Severity - Mishra, Punam; Khadka, Anupa; Parajuli, Sudip (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Introduction: Acne is one of the common problems in the adult female population. Androgen excess, indicated by high serum testosterone levels, has been implicated as a cause for adult-onset acne, though studies correlating testosterone levels with acne severity have shown varying results. Objectives: To assess serum testosterone levels in adult acne patients and correlate it with acne severity. Materials and Methods: This was a single-center, hospital-based, cross-sectional, descriptive study conducted in the Department of Dermatology and Venereology, Tribhuvan University Teaching Hospital (TUTH) from June 2023 to May 2024. All the adult female acne patients fulfilling the inclusion criteria visiting the Outpatient Department (OPD) were included in the study. Acne severity was assessed using the Adult Female Acne Scoring Tool (AFAST: score A and score B). Serum testosterone was measured using a chemiluminescent assay (CMIA), and the correlation of serum testosterone levels with the severity of acne was analyzed. Results: Among 51 female adult acne participants, the mean age of patients was 30.56 ± 0.74 years, median duration of acne of 7 months (1-180 months). The majority of participants had late-onset acne at 72.5% (n=37). Grade 2 acne was the most common, with the cheeks being the most frequently affected area. The mean serum testosterone level was 42.30 ± 15.71 ng/dl; none of the patients exceeded the normal range (5.17-77ng/dl). No significant correlation was observed between serum testosterone levels and acne severity according to the AFAST Score A (p=0.643) and Score B (p=0.830). The study’s findings should be interpreted cautiously due to its small sample size and lack of a control group, resulting from financial limitations. Conclusion: Serum testosterone levels are not a reliable marker of androgen excess in adult females with acne, and there is no significant correlation between serum testosterone levels and acne severity in this sub-population.